PENGGUNAAN E-MONEY BRIZZI SEBAGAI ALAT PEMBAYARAN MENURUT HUKUM EKONOMI SYARIAH (STUDI ANALISIS TERHADAP PRODUK E-MONEY BRIZZI PADA BANK BRI KANTOR CABANG BLORA) - Muhammad Zubaidi, Muhammad; Suhartono, Suhartono (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2020)
ABSTRACTThis research discusses and analyzes the mechanism of using Brizzi E-money issued by BRI Bank Blora Branch Office, as well as the perspective of Sharia Economic Law on the use of the card mechanism. Especially the electronic payment instruments issued by Bank BRI namely E-Money Brizzi. This research not only examines law theoretically, but also looks at it from the practice and application side in the field. This type of research is field research, namely research activities carried out at BRI Bank Blora Branch Office. The research approach which used is a qualitative descriptive research approach, which is an approach used to understand the phenomena about what is experienced by the subject and object of research.The results of this study concluded that the use of Brizzi E-money cards had met the legal and legal requirements for consent. In addition, when viewed from the aspect of cases that in validate the legality of the sale and purchase law, the use of Brizzi e-money cards in the sale and purchase transaction does not include elements that cancel the sale and purchase such as elements of gharar, maysir, and usury. The deduction of administrative funds due to transactions using the Brizzi e-money card has a similarity to the wakalah bil ujrah system in Sharia Economic Law. However, base on the results of the analysis conducted by the author, it is found that th euse of Brizzi e-money cards is not in accordance with the theory of wadi'ah dueto the unfulfillment of conditions and harmony in theuse, alsois not in line with the concept of wadi'ah yad amanah and wadi ' ah yad dhamanah from the aspect of the burden of responsibility for the party entrusted. Besides that, the use of Brizzi e-money cards is also not in accordance with the qardh theory. This is because in addition to not fulfilling one of the pillars and qardh validity requirements, also in the qardha fter the contract is said, the goods or asset swhich become the object of qardh automatically be come the property of the party receiving the loan. Where as in the system of using Brizzi e-money cards, the electronic money that is on the card after being deposited to the bank remains the property of the card holder.Â Keywords: E-Money, Brizzi, Sharia Economic Law, BRI Bank